2016
DOI: 10.1016/j.ophtha.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Incidence of Macular Edema after Cataract Surgery

Abstract: Pseudophakic macular edema occurs commonly after phacoemulsification cataract surgery, even in the absence of complications and risk factors. This large retrospective study using structured EMR data quantified the RRs of PME and the risk with increasing ETDRS severity of DR. It highlights the need for prophylactic therapy, especially in those groups of eyes with the highest RRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
263
0
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 330 publications
(315 citation statements)
references
References 22 publications
12
263
0
18
Order By: Relevance
“…In the context of cataract surgery, we have recently reported on a multicentre database study of 81 984 eyes undergoing cataract surgery in the UK 9. The UK National Health Service (NHS) is an ideal setting for this study, because it serves more than 90% of the population for cataract surgery, and there has been widespread adoption of EMR systems that mandate collection of detailed standardised datasets developed by The Royal College of Ophthalmologists 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of cataract surgery, we have recently reported on a multicentre database study of 81 984 eyes undergoing cataract surgery in the UK 9. The UK National Health Service (NHS) is an ideal setting for this study, because it serves more than 90% of the population for cataract surgery, and there has been widespread adoption of EMR systems that mandate collection of detailed standardised datasets developed by The Royal College of Ophthalmologists 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…Being diabetic increased the risk to 1.8 times, and having Diabetic Retinopathy (DR) increased the risk to 6.23 times. A greater chance of ME development was seen with increasing severity of DR 11. Kwon SI et al showed that 18% of diabetic patients developed transient ME, with 68% showing resolution after 6 months of surgery 2…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of this syndrome reported to be multifactorial. Its incidence is higher in patients with vasculopathy, hypertension, uveitis [2][3][4]. IrvineGass syndrome is usually self-limiting and spontaneous resolution occurs within 3-6 months [5].…”
Section: Introductionmentioning
confidence: 99%